Upaya Pencegahan Cidera Fisik Pada Anak Dengan Epilepsy Di Rsud Pandan Arang Boyolali - Adi Nugroho, Alib, Irdawati, S.Kep.,Ns.,M.Si.,Med (2016)
Epilepsy is a disorder of the central nervous order characterized by the occurrence of the spontaneous generation and periodically recurring seizures is Epilepsy,with or without a clear cause of the intervals of attacks over 24 hours,due to excessive electrical charge off in the neurons of the brain. Epilepsy is a disease that his attack came unexpectedly or suddenly,and potentially to the onset of trauma in children. Epilepsy is also potentially lead to physical injuries,weaknesses in physical and unconsciousness. Therefore required a long treatment and education towards sufferers and families,if not immediately overcome epilepsy will badly a child's behavior and development will also have an impact on health (physical injury). To minimize physical injuries on the child needed health education on the family about the handling and treatment of children at seizure. The aim is to describe the anticipating, preventing and minimizing physical injuries in children. The presence of health education to parents and the client expected parents understand the consequences of the disease epilepsy,understand the signs and symptoms,and understand the factors its originators so parents can keep an eye on the child properly. This method is applied in accordance with the nursing care on patients with epilepsy cases. One of the actions that can be performed independently on the patient's epilepsy that is preventing the physical injuries in children by way of health education to the family about the prevention and treatment of the child when the seizures. Data collection was conducted by assessment or interviews with the parents and with the literature record medical records,doctor's notes, notes,notes of nursing lab,and by supporting other outcomes. The effort that has been made in the giving of information to the families about prevention and treatment of the child when the spasms can be resolved. So it can be inferred that the handling of the cases of epilepsy with IE problem is fixed,the intervention followed by advocating to parents at a time when the House gave first aid at the time of seizure and supervise the child properly